2016
DOI: 10.1001/jamainternmed.2016.3324
|View full text |Cite
|
Sign up to set email alerts
|

Association of Blood Donor Age and Sex With Recipient Survival After Red Blood Cell Transfusion

Abstract: ed blood cell (RBC) transfusion is the most common medical procedure in contemporary medicine. 1 In the United States, 7.6% of all hospitalized patients will receive at least 1 blood transfusion during their hospitalization, and its use has increased between 1997 and 2011 by 134%. 1 With the main objective to improve oxygen delivery to tissues, 2 RBC transfusion is used in a variety of medical situations, ranging from correction of chronic low-grade anemia to resuscitation of the massively bleeding patient. 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
166
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(173 citation statements)
references
References 43 publications
5
166
2
Order By: Relevance
“…Furthermore, the authors speculate that residual confounding, likely patient underlying disease severity, due to imperfect measurement of the confounding variable leading to its incomplete removal, may account for the positive results observed in other studies. These results were contrary to those observed by Chassé et al (4). As per eTable 10, the deleterious effects of EPF RBCs remained, again in the younger males, after controlling for the cumulative number of plasma and platelet units received.…”
contrasting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, the authors speculate that residual confounding, likely patient underlying disease severity, due to imperfect measurement of the confounding variable leading to its incomplete removal, may account for the positive results observed in other studies. These results were contrary to those observed by Chassé et al (4). As per eTable 10, the deleterious effects of EPF RBCs remained, again in the younger males, after controlling for the cumulative number of plasma and platelet units received.…”
contrasting
confidence: 85%
“…Other policies and advances in cell preservation technology such as ABO and Rh matching, leukoreduction and limitations in the age of storage (to the age of RBC viability) of blood products have decreased recipient morbidity and mortality (1)(2)(3). However, the concept that RBC donor female gender and parity may influence recipient mortality has been a subject of much debate in the blood banking community and differing conclusions are reported in several large retrospective studies (4,5). Here we comment on the recent article by Caram-Deelder et al (6) published in JAMA reporting increased mortality in male recipients of RBC units from female donors who had ever been pregnant compared with male recipients of RBC units from male donors.…”
mentioning
confidence: 99%
“…22 The second study, based on Canadian data, used a more complex, time-dependent survival model and conversely reported increased risks of death among recipients of blood from young and female donors. 21 The difference between the findings of these 2 studies is striking. If the Canadian findings are true, they would have immediate implications for transfusion medicine practice.…”
mentioning
confidence: 85%
“…Most recently, following reports from animal model studies suggesting that transfusions from young donors may have rejuvenating effects in older recipients, [15][16][17][18][19][20] there have been at least 2 observational studies investigating whether donor age influences the survival of patients receiving transfusions. 21,22 The studies used dissimilar statistical methods and reported conflicting results. In the first study, which was based on the Scandinavian Donations and Transfusions (SCANDAT2) database, 23 a matched cohort design was used, and no associations were found between donor age and mortality of patients who received transfusions.…”
mentioning
confidence: 99%
See 1 more Smart Citation